ANALYSIS OF THE DEVELOPMENT OF ISLAMIC FINANCE IN CASH WAQF PRACTICES THROUGH ISLAMIC FINANCIAL INSTITUTIONS IN INDONESIAN - Harley Agustian; Chairul Bariah (PT. Radja Intercontinental Publishing, 2024)
This research is motivated by the condition and development of Islamic finance in the practice of cash waqf at Islamic Financial Institutions through BWI by giving rise to Islamic financial innovation, namely CWLS through SWR products. In the report received, SWR001 to SWR004 have been launched, based on data that has been analyzed cash waqf receipts through this program have experienced a significant increase. This research measures the performance of receiving cash waqf practice reports through the BWI LKS. This research is a type of quantitative research using the common size analysis method on SWR001 products against SWR002 and SWR003 against SWR004. The results of this research show that, overall, the practice of cash waqf has experienced an extraordinary increase through the development of Islamic finance, namely Retail Waqf Sukuk (SWR). In the SWR004 product there was a large increase, namely 74.64% with a nominal value of IDR 112,563 billion with a total of 709 waqifs. The latest finding in this research is the discovery of 3 strong pieces of evidence regarding waqifs on the total receipts of cash waqf. This also shows that the greater a person donates the assets he loves, the greater the virtue he will gain. This virtue can make a person more generous and a good person, better than before.